The Relation of Photography, Public Policy, and the Transformation of Public Spaces in Jakarta - Tahalea, Silviana Amanda Aurelia; Novianti, Erliana; Rahmadani, Siti Febrina; Gitoprakoso, Leonardus Aryo (Gondang: Jurnal Seni dan Budaya, 2024)
Photography is a powerful tool for capturing and conveying stories, emotions, and experiences, and it holds significant potential to influence public awareness and policy. This research investigates the impact of photography on public space infrastructure in Jakarta. It aims to explore how photography shapes public space infrastructure, affects public perception, and raises awareness of policy issues, while also evaluating its role in mobilizing support for policy changes. The study contributes to understanding the relationship between photography and public policy, integrating visual theory, critical theory, and communication studies. The hypothesis is that photography significantly impacts the public policy-making process and outcomes. Using qualitative methods such as observation, content analysis, and data collection representing subjects' reactions and behaviors, along with photographic content analysis, this research seeks to offer a comprehensive understanding of how visual images influence public opinion, enhance awareness, and affect policy debates. The study also includes a critical analysis through Spatial Critical Theory to clarify the dynamics between urban development, public space usage, and public policy in Jakarta. This research aligns with the author’s academic focus on photography's role in urban culture and architecture, complementing the course on Architecture and Interior Photography taught by the lead researcher. The findings aim to provide insights into photography's role in shaping public policy and facilities, offering practical implications for policymakers, photographers, and the public in leveraging photography for policy advocacy and public facility enhancement.